2023
DOI: 10.3390/su15129830
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the Pilot Free Trade Zone and Chinese Green Total Factor Energy Efficiency

Abstract: In the context of China’s “double carbon” target, paying attention to regional green total factor energy efficiency (GTFEE) is crucial for ensuring a fundamental guarantee for China’s free trade zones for the promotion of sustainable development in China’s free trade zones. However, the existing literature lacks focus on the environmental effects of these zones. This study takes advantage of the pilot free trade zone (PFTZ) implemented in 2013 as a natural experiment, utilizing panel data from 2009 to 2020 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…strengthening the connotation of these zones. However, most existing policy evaluation studies have focused on exploring the economic effects of coastal PFTZs [7,8]. Whether the PFTZs along the YREB can replicate the institutional innovation achievements of coastal PFTZs remains a subject for further research.…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations
“…strengthening the connotation of these zones. However, most existing policy evaluation studies have focused on exploring the economic effects of coastal PFTZs [7,8]. Whether the PFTZs along the YREB can replicate the institutional innovation achievements of coastal PFTZs remains a subject for further research.…”
Section: Plos Onementioning
confidence: 99%
“…Empirical studies by Jiang et al [37] and Ma et al [38] on the Shanghai PFTZ revealed significant institutional dividends and a positive correlation between PFTZs and GTFP, albeit with diminishing effects over time. Furthermore, Chang et al [2] found that the establishment of PFTZs significantly fosters regional green and high-quality development, while Zhang and Zhou [8] identified that PFTZs enhance regional green total factor energy efficiency through industrial structure upgrades and promotion of green technological innovation.…”
Section: Pftz Policy Impact On Urban Green Developmentmentioning
confidence: 99%
See 2 more Smart Citations